Incidencia de depresión y su impacto en el estado nutricional en adultos mayores, en el Centro Programa Geriátrico del cantón Puyango durante el periodo febrero - julio 2016. - Ramón Álvarez, Verónica Judith (2017)
Every stage of life demands care, but it is in the latest stages when attention and care are unavoidable, since in addition to the physical deterioration, in most cases are added depressive states, being a reality that malnutrition and depressions go hand in hand, together they are the most destructive factor of the quality of life of the elderly. The present study aimed to determine the incidence of depression and its impact on nutritional status in the elderly in the center "Geriatric Program canton Puyango" in turn identify the presence of the depressive state in relation to age, sex, marital status; to determine the nutritional status of the elderly who present depression and to construct a proposal of prevention of depression. The sample consisted of 48 elderly and a descriptive, transverse and cross-national design was used, including the use of the Yesavage test and MNA (Mini Nutritional Assessment). The population of elderly adults in Ecuador was 1'235.704 in 2010, with an average age of 71.3 years, for both men and women, in the study carried out in the geriatric program of Puyango Canton, the mean age was 76.54 years. The overall incidence of depression after applying the Yesavage test was 100% for mild depression in geriatric patients aged 75-84 years old and 66.7% for depression in participants aged 85 and over. Multiple risk factors for the development of depression have been identified, such as the female gender since depression in women is more prevalent, but its difference with respect to men decreases with age, so that according to the areas in such a way that according to the scopes they can come to match. In our population, 87.5% were women and 12.5% were men, of whom mild depression was greater in men with 100% compared to women who had 64.3% while the established depression was present in the female gender with 35.7%. Key words: Depression, Nutritional Status, Elderly adults.